Peran Trichoderma reesei E. G Simmons pada Pengendalian Damping-Off Semai Cendana (Santalum Album Linn.) - S. M. Widyastuti; M. Hariani (Jurnal Perlindungan Tanaman Indonesia, 2006)
The sandalwood seedling has been planted in the nursery of Balitbang Kehutanan NTT to experience the destruction is about 20%, seedling is attacked by  damping-off. Biological control has been developed as alternate method against soil born diseases to eliminate  damage  on the environment. One of  the biological  agents  having high  antagonistic potential against soil born pathogen is Trichoderma spp. The direction of experiment  to search the cause of lodoh on the sandalwood  seedling and the application influences T. reesei on the control lodoh in the sandalwood seedling. Methods  of  the experiment was (1) isolation the sandalwood seedling of  painful and soil example  from NTT, (2) Postulat Koch test on the sandalwood seedling, (3) antagonistic test of T.  reesei  in vitro and (4) effectiveness  test of T. reesei against developing patogen in vivo. The result indicated that lodoh on the sandalwood seedling caused by Fusarium sp. T. reesei in vitro inhibited Fusarium sp. at average of 100% accordingly. The application of T. reesei as biological control agent against Fusarium sp. showed high  effectivity. The attact percentage of lodoh on sandalwood seedlings showed that the lowest one was growth on compost formulated with T. reesei (5%), whereas seedlings growth on compost without T. reesei,  unsteril  sands and soil samples  from NTT were 30%, 35% and 65%.